Blue shift in the optical bandgap of tin oxide thin films by controlling oxygen-to-argon gas flow ratio - Meenakshi; Gautam, Sanjeev; Chae, Keun Hwa; Lee, Ik-Jae; Shin, Hyun-Joon; Thakur, Anup (WORLD SCIENTIFIC PUBL CO PTE LTD, 2015)
Tin oxide (SnO2) thin films were deposited by radio-frequency (RF) magnetron sputtering on silicon and glass substrates at different oxygen-to-argon gas-flow ratio (O-2-to-Ar = 0%, 10%, 20%, 30% and 50%). All films were deposited at room temperature and fixed working pressures, 10 mTorr. X-ray diffraction (XRD) measurement suggests that all films were crystalline in nature except film deposited only in argon environment. The transparency of all of the films was more than 85% in the visible range except the film deposited only in the argon environment. Atomic force microscopy results showed that the surface of all the films were highly flat and smooth. The optical bandgap, estimated by Tauc plot was increased with oxygen environment. Blue shift was observed in the absorption edge and was accounted to decrease in the oxygen vacancies and dangling bonds.
Keywords: SUBSTRATE-TEMPERATURE; PRESSURE